DIGITAL INFLUENCE: EXAMINING THE IMPACT OF LIVE AND VIRAL CONTENT ON CUSTOMER PURCHASE INTENTION - Citra Aditya Kusuma; Frenisya Atuna (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The increasing dominance of social media has positioned live streaming and viral marketing as influential strategies in shaping customer purchase intention. Methods: This study examines the combined effects of these strategies through the lens of the Elaboration Likelihood Model (ELM), which distinguished between central and peripheral routes of persuasion. While prior research has explored these approach individually, their joint impact remains underexamined. To address this gap, a quantitative approach was employed by collecting data from a survey of 100 Generation Z TikTok users. Results: Multiple linear regression analysis revealed that live streaming content, associated with central route processing, has a stronger positive effect on purchase intention (ß=0.621;p<0.001) compared to viral marketing which operates via peripheral cues (ß=0.285;p=0.002). These findings suggest that marketers targeting Generation Z should strategically integrate rational message elements and emotionally engaging content to optimize user engagement and drive conversion. The study contributes to the broader discourse on digital marketing literature and offers strategic implications for enhancing conversion in social media-driven environments. Keywords: Digital marketing, live streaming, purchase intention, viral marketing